OPTIMASI STRUKTUR HELIDECK DENGAN VARIASI BEBAN HELIKOPTER - Anwar Anwar; Reza Bachmid (Construction and Material Journal, 2020)
Helideck is a helicopter landing field located on ships and offshore buildings. The helideck structure must have the strength to withstand the loads of the helicopter landing. The purpose of this study is to determine the maximum strength of the helideck structure. Helideck structure strength calculations used SACS structural strength software by performing a running analysis adopting the finite element method. The maximum calculation results value that the helideck structure can hold is the type of helicopter with a maximum weight of 155 kN with a working stress of 37,80 N/mm2 and an interaction value of (IR) 1. The helideck structure will encounter a yield stress or fracture with an IR value > 1. Keywords : Structure Strength, Helideck, Helicopter Load.